FORMULASI DAN UJI TOTAL ANTOSIANIN SEDIAAN BATH BOMB DARI SERBUK SARI KULIT BUAH NAGA MERAH (Selenicereus monacanthus L.) - Wafiq Azizah, Nanda; Putri Wiyati, Eka; Yanuarto, Tri (Jurnal Komunitas Farmasi Nasional, 2025)
ABSTRACT Red Dragon Fruit Peel (Selenicereus monacanthus L.) is often considered waste, even though it contains bioactive compounds such as anthocyanins with high antioxidant activity. This study aimed to formulate bath bomb preparations from the red dragon fruit peel pollen (Selenicereus monacanthus L.) and to evaluate their physical properties and total anthocyanin content. The formulations were made with varying pollen concentrations of 5%, 7.5%, and 10%, followed by organoleptic, pH, dissolution time, foam height, stability, and qualitative and quantitative anthocyanin tests using the UV-Vis spectrophotometry method. Organoleptic testing showed that F3 (10%) had the most intense color, characteristic aroma, and solid form. In the pH test, F1 (5%) was the most stable formula and met the bath bomb pH range (8–11). All formulas met the dissolution time requirement (<5 minutes), with F2 (7.5%) showing the most optimal dissolution time among the pollen-containing formulas. In the foam height test, only F3 (10%) met the foam height criteria. Stability testing using the cycling test method showed that F3 had the best color, shape, and aroma stability over six storage cycles. Determination of total anthocyanin content showed that F3 (10%) had the highest level of 2.504 mg/L. Thus, it can be concluded that increasing pollen concentration enhances anthocyanin content and color stability but may affect pH reduction and foam formation. Keywords: Red dragon fruit peel; Pollen; Bath bomb; Anthocyanins